Optimalisasi Strategi Pemasaran Gula Jawa di UMKM Gula Merah Leugit Padukuhan Kabrokan Kulon - Kurnianingtyas, Chandra Dewi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Padukuhan Kabrokan Kulon is an Padukuhan located in Sendangsari Village, Pajangan District, Bantul Regency, Special Region of Yogyakarta. Padukuhan Kabrokan Kulon has a lot of potential in the field of tourism objects and natural resources. One of the potentials in the field of natural resources is palm sugar SMEs. However, due to limitations in communication, technology, access to information, and funds, the potential of the Kabrokan Kulon Padukuhan, especially the Java sugar MSMEs, is not being utilized to its full potential. Therefore, there is a need for empowerment through educational activities about packaging design for Javanese sugar SMEs, socialization of simple bookkeeping, and also empowering Javanese sugar SMEs through branding communication to Javanese sugar SMEs in Padukuhan Kabrokan Kulon. So that from the results of data collection, the servant chose the potential of natural resources in Padukuhan Kabrokan Kulon, namely Javanese sugar SMEs which were made and discussed in village potential, moodboards, packaging from besek, videos on the potential of Javanese sugar villages and simple bookkeeping. From the results of the video, it is hoped that it will be useful and the village's efforts to maximize village potential.